Identifikasi Hambatan Pada Penanganan Penanggulangan Kebakaran Di Wilayah Jakarta Timur menggunakan metode bowtie analysis dan A'WOT analysis - Fajar Septian; Tatan Sukwika; Maya Dewi Dyah Maharani (LPPM Institut Teknologi Petroleum Balongan, 2021)
Abstract. Increased population density, community activities, lack of infrastructure and people unable to cope with fires are fire-prone areas. This study aims to identify barriers to fire prevention in the East Jakarta area so that fires can be prevented and dealt with properly. This study uses a qualitative descriptive analysis method with content analysis, bowtie analysis and A'WOT analysis. The results show that the response time of the officers according to the target time reached 98% and 2% did not, the most fire objects were residential buildings 28%, 81% extinguished by officers and 19% extinguished by the community, the area that covers a radius of 2km from the 160.59Km2 fire post service has not been reached 27 ,44Km2. Bowtie's analysis shows the hazard of fire, the top event is limited in fire management supervision, the threat response time is more than 15 minutes the barrier increases the preparedness and skills of officers, uses an effective, fast, and accurate fire report application, the threat of lack of coverage area of the barrier post increases the number of fire stations. fires, providing fire extinguishers and hydrants. The A'WOT analysis shows the quadrant IV integration strategy, conditions that grow and develop. It can be concluded that the lack of service coverage areas and fire facilities and infrastructure in the community can inhibit fire fighting. The managerial implication is expected to increase the number of posts to support the punctuality of the response time of officers, facilitate socialization, training, fire simulations on a regular basis and thoroughly to the public so that they are more concerned about the threat of fire hazards. Keywords: Officer response time, fire department service coverage area, fire prevention and control